Strengthening Village-Owned Enterprises (BUM Desa) and Joint Village-Owned Enterprises (BUM Desa Bersama) with Corporations - Sulistyorini, Harlina; Setiawan, Margono; Sumiati, Sumiati; Wijayanti, Risna; Basuki, Ananto (AIBPM Publisher, 2023)
BUM Desa/BUM Desa Bersama requires guidance and development from government and private sectors. BUM Desa/BUM Desa Bersama can cooperate with corporations for its future development. This study aims to formulate an effective collaboration model between BUM Desa/BUM Desa Bersama and corporations that contains the following substances: 1) Identifying and analyzing the need for collaboration for BUM Desa/BUM Desa Bersama with corporations; 2) Identifying obstacles in collaboration between BUM Desa/BUM Desa Bersama and corporations; 3) Formulating effective solutions in overcoming the obstacles that arise; 4) Finding lessons learned and success factors; and 5) Formulating a collaboration model for BUM Desa/BUM Desa Bersama with corporations. This study is a collaboration between BUM Desa in Malang Regency and Batu City with a corporation that is only limited to agents-based services. BUM Desa is an extension of the corporation’s business ventures in rural areas. Financial income from the collaboration is less significant, so it is said to be the social goal of BUM Desa. This collaboration does not pose a problem since BUM Desa represents the corporation's interest and acts as directed. BUM Desa does not make policies and decisions that can increase its own profits. This collaboration is not entirely detrimental to BUM Desa, but does not contribute enough and has an economic impact on improving the village’s community welfare.